From knowledge encoding to procedural generation for early-stage layout design: A case of linear shopping centres - Baizhou Zhang; Biao Li (Frontiers of Architectural Research)
This paper presents a rule-based procedural generation approach for layout design by design knowledge encoding. Taking linear shopping centres as example, the proposed method encodes the layout design elements of the walkway space, tenant areas, and staircases into generative rules based on geometric operations. The generative rules integrate the shopping centre layout's spatial patterns and geometric features and incorporate user-specified interaction parameters to form a generation tool prototype for early-stage layout design. The results show that the method can deal with the complex spatial elements of linear shopping centres and provide design references for architects, which helps combine generative algorithms with the design process.